Fostering Naturalistic Intelligence in Early Childhood: An Exploratory Study of Learning Strategies, Practices, and Developmental Outcomes - Deswati,; M. Havis,; Hamdan sakirin,; Jum'ah, Muhibatul; Umar,; M. Iriyansyah, (Jurnal Paedagogy, 2026)
This study aims to describe the development of naturalist intelligence among early childhood learners at KB Titian Sejahtera, Muaro Jambi Regency, by examining learning implementation, instructional strategies, learning activities, supporting and inhibiting factors, and developmental outcomes. The study employed a qualitative descriptive approach. The participants consisted of the school principal, two teachers, and 26 children. Data were collected through classroom observations, semi-structured interviews, and document analysis. Data credibility was ensured through source, method, and time triangulation, while data were analyzed using data reduction, data display, and conclusion drawing and verification. The findings indicate that naturalist intelligence was systematically developed through nature-based learning by utilizing the school environment as a primary learning resource. Teachers implemented outdoor learning, environmental exploration, play-based learning, and the use of natural materials such as leaves, flowers, stones, and seeds. Supporting factors included a conducive school environment, teacher creativity, institutional support, and children’s enthusiasm, whereas limited learning materials, weather conditions, time constraints, and insufficient parental involvement were identified as major challenges. The findings further demonstrate that this approach not only enhances children’s ability to recognize and classify natural objects but also fosters environmental awareness and responsibility. Moreover, the effective use of the school environment as a learning resource highlights the potential of place-based education and ecopedagogy as meaningful approaches to early childhood education, particularly in rural settings with limited access to digital technologies and modern educational facilities.